2018
DOI: 10.1590/0100-29452018544
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and brassinosteroid effect on strawberry ripening after field spray

Abstract: -In contrast to ripening of climacteric fruits knowledge, non-climacteric fruits ripening still poorly understood. In this sense, strawberry (Fragaria x ananassa L. Duch) is a high commercial crop and has an expressive world production that has been used as a model study. Thus, the aim of this study was to evaluate the effect on physicochemical and phytochemical characteristics of strawberry Cv. Camiño Real, in four maturation stages (green, white, pink and red) after the ethylene (Etephon®) and brassinosteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, in the present study, fruit remained on the plant and were not subjected to the stress of removal. Another possible response to detachment is the increase in phenolic compound content that was stimulated by ethylene treatment in detached green and white strawberry fruit (Lopes et al, 2015;Ayub et al, 2018b), while 1-MCP treatment reduced phenolic content (Villarreal et al, 2010). Treatment of fruit in situ in the present study had no effect on total phenolics regardless of the developmental stage at which the treatment was applied.…”
Section: Ethylene Effect On Strawberry Fruit Ripeningmentioning
confidence: 55%
See 1 more Smart Citation
“…However, in the present study, fruit remained on the plant and were not subjected to the stress of removal. Another possible response to detachment is the increase in phenolic compound content that was stimulated by ethylene treatment in detached green and white strawberry fruit (Lopes et al, 2015;Ayub et al, 2018b), while 1-MCP treatment reduced phenolic content (Villarreal et al, 2010). Treatment of fruit in situ in the present study had no effect on total phenolics regardless of the developmental stage at which the treatment was applied.…”
Section: Ethylene Effect On Strawberry Fruit Ripeningmentioning
confidence: 55%
“…Due to low rates of ethylene production and respiration during ripening, strawberry fruit are classified as nonclimacteric (Barry and Giovannoni, 2007;Bapat et al, 2010). However, recent studies have suggested ethylene (Trainotti et al, 2005;Iannetta et al, 2006;Bapat et al, 2010;Villarreal et al, 2010;Merchante et al, 2013;Sun et al, 2013;Lopes et al, 2015) and its interaction with other plant growth regulators such as abscisic acid (Jia et al, 2011;Symons et al, 2012;Jia et al, 2013;Ayub et al, 2016;Jia et al, 2016;Tosetti et al, 2020) and brassinosteroid (Ayub et al, 2018b;Ayub et al, 2018a) may affect strawberry fruit ripening.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing photosynthetic activity under stress conditions reduces levels of sugar content in the plant.The use of 24-Epibrassinolide in conditions of stress leads to a rise in the levels of sugar in the plant (Swamy et al, 2014 plants increases the levels of biochemical reactions associatedwith the conversion of glucose from the kelvin cycle to move towards developing fruits and subsequently increase the soluble and in soluble sugars in the fruits (Ramani, 2015).Titratable acidity is concentration of organic acids in fruit which is one of the important parameters for assessing the quality of fruits (Akhtar et al, 2010).Under high temperatures, the titratable acidity of fruits decreased significantly in both cultivars.At high temperatures, organic acids are used as substrates in the respiratory process, which reduces the titratable acidity under thermal stress conditions (Lotfi et al, 2016).In the present study, heat stress did not lead to a significant reduction in the phenolic compounds of Gaviota and Parus cultivars compared to the control treatment, which was probably due to the high stimulation of the phenylpropanoid pathway under stresscondition. Ayub et al (2018) reported the phenylpropanoid pathway and the accumulation of phenolic compounds can be stimulated as a physiological response to a stress condition. The results of present study weresimilar tothe results of studies on grape berry (Xi et al,2013).Plants that were treated with 24-Epi brassinolideunder heat stress condition accumulated more phenolic compounds.24-Epi brassinolide treatment helps to increase the activity of the phenylalanine ammonia-lyase enzyme, which is the enzyme necessary to start the synthesis of free phenols (Champa et al, 2015).The use of 24-Epi brassinolide solution in Parus cultivar stimulated the synthesis of antioxidant compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the use of 24-Epi brassinolide solution under heat stress condition increased the amount of anthocyanin synthesis in both cultivars, which seems to be due to the increased activity of phenylpropanoid in these two cultivars under heat stress condition. In strawberry, brassinosteroid application increases the expression of transcription factors and positively affects the amount of anthocyanin synthesis through interference in the phenylpropanoid pathway (Ayub et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent article [ 22 ] focused on non-climacteric fruits and the effect of BRs/ethylene on their ripening. In this work, strawberries were used as a model study of non-climacteric fruits and they were treated with an exogenous spray of ethylene (ethephon) and EBL.…”
Section: Ripening and Postharvest Development Of Fruitmentioning
confidence: 99%